2016
DOI: 10.5005/jp-journals-10005-1369
|View full text |Cite
|
Sign up to set email alerts
|

Primary Oral Health Care in India: Vision or Dream?

Abstract: The contemporary approach to dental caries management in children focuses on prevention than treatment. Pediatricians, general dentists and pediatric dentists must be involved in a detailed preventive program, which includes prenatal counselling, treatment of expectant mothers at risk for dental caries, infant oral health care and the establishment of the dental home, so that dental disease can be prevented in infants, starting at a young age.Various health care system and organizations in India must join toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Why integration was a failure: In this review, it was seen that integration fails in some places of North Carolina and California because of lack of integrated HER that prevents all health care providers from seeing a patient's common care plan and treatment status. [14] In an article by Filho, critical thinking was required to ensure proper implementation of the principles of unified health system in Brazil. [25] In an article by Joskow, models of care and delivery and payment systems have not substantially integrated oral health in overall health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why integration was a failure: In this review, it was seen that integration fails in some places of North Carolina and California because of lack of integrated HER that prevents all health care providers from seeing a patient's common care plan and treatment status. [14] In an article by Filho, critical thinking was required to ensure proper implementation of the principles of unified health system in Brazil. [25] In an article by Joskow, models of care and delivery and payment systems have not substantially integrated oral health in overall health.…”
Section: Discussionmentioning
confidence: 99%
“…The definition states: “The dental home is the ongoing relationship between the dentist and the patient, inclusive of all aspects of oral health care delivered in a comprehensive, continuously accessible, coordinated and family centered way. Establishment of a dental home begins no later than 12 months of age and includes referral to dental specialists when appropriate.”[14]…”
Section: Medical–dental Integrationmentioning
confidence: 99%
“…Vertical colonization of Streptococcus mutans from mother to child is well documented. Studies have shown that these Streptococcus are initially acquired by children from their mothers at around 2 years of age, which is the window of infectivity [14].…”
Section: Primary Care and Oral Health In Childrenmentioning
confidence: 99%
“…Although the notion of integrated oral health care through a multi-disciplinary team approach has been touted as a key strategy to broaden the delivery of oral health promotion services ( 38 ), this seemingly uncomplicated patient/client centered initiative continues to face challenges in many parts of the world, as indicated earlier ( 39 , 40 ). The question begs: why is this so?…”
Section: Opportunities For Improved Oral Health Care Delivermentioning
confidence: 99%